RIGHT KIDNEY WITH AN ACCESSORY RENAL ARTERY: A CASE REPORT - Elhaj Mustafa, Dr. Amal Yousif Ahmed; Mohammed Alasmari, Dr. Wardah Abdullah (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Knowledge of the variation of renal vascular anatomy has importance in exploration and treatment of renal trauma, renal transplantation, angioplasty or vascular reconstruction. The renal arteries typically originate from the anterolateral aspect of the abdominal aorta at approximately the level of the L1 and L2 vertebral bodies just below the origin of the superior mesenteric artery (1, 2). These two end arteries carry nearly 25% of the cardiac output to the kidneys (1). Usually there is only one right renal artery and one left renal artery penetrating the hila of each kidney. Renal artery variations are common in the general population and the frequency of variations shows social, ethnic, and racial differences (3, 4). It is more common in Africans (37%) and Caucasians (35%), and is less common in Hindus (17%) and the populations except Caucasians (18%). The frequency of extra renal arteries (ERA) shows variability from 9% to 76% and is generally between 28%–30% in anatomic and cadaver studies (3, 5, 6). Renal artery variations are becoming more important due to the gradual increase in interventional radiological procedures, urological and vascular operations, and renal transplantation (5, 8).